Proyecto de fortalecimiento institutional sobre manejo del recurso agua en la region AndinaProject on Institutional Strengthening for Water Management in the Andean Region. Six-month progress report, No.1, 28 March - 28 September. In Spanish - Garcés-Restrepo, C. (International Irrigation Management Institute, 1995)
Annex 6 of 7